Body Composition and Physical Health in Sports Practice - Toselli, Stefania (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Research on human body composition has gained relevance given the recognized health impact of several body components. Many contemporary scientists have contributed to the field of body composition research as it exists today, even though interest in the topic extends back several thousand years. Quantifying human body composition in sports practice plays an important role in monitoring athletes' health status, performances, and training regimens. Such analysis can be performed in different contexts and with different approaches-e.g., in cross-sectional studies that aim to characterize sporting group samples and in longitudinal research finalized to define short-term or long-term changes and implications for physical health and performance. Body composition is also fundamental for a correct interpretation of body mass and weight status to plan specific interventions. This book adds new information on the effect of body composition on physical health and sport performance, current body composition measurement techniques and strategies for improving physical health through sports practice.